2018
DOI: 10.5021/ad.2018.30.6.708
|View full text |Cite
|
Sign up to set email alerts
|

Concurrence of Circumscribed Morphea and Segmental Vitiligo: A Case Report

Abstract: Although a few reports have noted the concurrent presentation of morphea and vitiligo at distinctly separate sites in the same patient, it is extremely rare that these two conditions occur at the same sites in a patient. We report the case of a 10-year-old Korean girl with morphea and vitiligo and those lesions occurred at the same sites and progressed simultaneously. An autoimmunity and a cutaneous mosaicism was considered to be involved in such an unique presentation as the pathogenesis is concerned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…11 different reports were found which makes it by far the most frequently observed comorbidity [57.1% (12/21 patients) of reported patients with autoimmune comorbidities]. In most cases, the morphea lesions affected the same body area as the SV, although multifocal morphea was also documented (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Cases with lichen striatus are interesting because of the striking similar pathogenesis (48) (Figure 1).…”
Section: Cases Of Segmental Vitiligo Displaying Additional Skin Disormentioning
confidence: 99%
“…11 different reports were found which makes it by far the most frequently observed comorbidity [57.1% (12/21 patients) of reported patients with autoimmune comorbidities]. In most cases, the morphea lesions affected the same body area as the SV, although multifocal morphea was also documented (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Cases with lichen striatus are interesting because of the striking similar pathogenesis (48) (Figure 1).…”
Section: Cases Of Segmental Vitiligo Displaying Additional Skin Disormentioning
confidence: 99%
“…A review of the literature revealed an additional nine pediatric cases with the cooccurrence of segmental vitiligo and morphea for a total of 10 cases, including the case described in this report (Table 1). [5][6][7][8][9][10][11][12] The median age at diagnosis was 10 (range 8-18 years). Six out of 10 of the cases were female.…”
Section: Discussionmentioning
confidence: 99%
“…Brazilian Journal of Health Review, Curitiba, v. 7, n. 1, p. 2612-2620, jan./fev., 2024 A Esclerodermia ou Esclerose Sistêmica é uma doença sistêmica, heterogênea e complexa cuja patologia envolve inflamação e fibrose da pele e tecidos extracutâneos. 3,7 Embora a causa ainda não seja totalmente esclerecida, acredita-se que fatores genéticos, combinado à um evento desencadeante primário estejam envolvidos na gênese da doença, levando à anormalidades das células endoteliais e inflamação perivascular.…”
unclassified
“…As hipóteses incluem mosaicismo cutâneo e atuação auto imune. Tem se a hipótese de que durante a embriogênese há exposição a gatilho que ativaria a auto imunidade, que causaria o desenvolvimento de esclerodermia e vitiligo 3,12.…”
unclassified